Spherical graphite material as well as preparation method and application thereof
The carbon precursor powder is processed by high-temperature plasma heat treatment to prepare spherical graphite materials with high tap density, graphitization degree and low orientation, which solves the problem of large expansion of graphite negative electrode materials in the prior art, and achieves high capacity, High head efficiency and excellent expansion performance.
Patent Information
- Application Number
- CN202310930913.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has the problem of large expansion when preparing high-performance graphite anode materials for lithium-ion batteries, and poor processing performance, resulting in low cell production efficiency and reduced energy density.
The carbon precursor powder is processed by high-temperature plasma heat treatment to achieve graphitization, spheroidization and impurity separation of coke powder, and a spherical graphite material with high tap density, high graphitization degree, high purity and low orientation are prepared.
The spherical graphite material exhibits high capacity, high first-time Coulomb efficiency and excellent expansion performance, improving the overall performance of the negative electrode material of lithium-ion battery.
Smart Images

Figure CN119409182A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a spherical graphite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy industry, the demand for high-performance graphite negative electrode materials for lithium-ion batteries is increasing. Artificial graphite negative electrode materials prepared with coke as raw material are favored due to their excellent rate performance and high initial efficiency. However, due to the large orientation of coke powder, artificial graphite prepared with coke powder as raw material has the problem of large expansion when used in lithium-ion battery negative electrode materials.
[0003] The prior art documents are as follows:
[0004] CN103214245A discloses a method for preparing a carbon / carbon composite microsphere material. The method firstly mixes a binder, coke powder particles with a particle size less than 2 μm, carbon black, and a solvent in a certain proportion to prepare a slurry, then prepares initial composite microspheres through a spray drying process, and then further heat treats the slurry.
[0005] CN111792640A discloses a method for preparing a spherical low-expansion high-capacity graphite negative electrode material. The method comprises mechanically mixing primary particles with a first additive in a certain proportion, adding a second additive, and then heat treating the mixture so that the additive bonds the primary particles into spherical secondary particles to obtain a spherical low-expansion high-capacity graphite negative electrode material.
[0006] CN105977473A discloses a method for preparing composite microspheres from anthracite-based graphite particles and graphene flakes by spray granulation. Summary of the invention
[0007] After in-depth research, the inventors of the present invention surprisingly found that:
[0008] The technical solution of CN103214245A requires that the particle size of the coke powder is relatively small, which is not applicable to the preparation of high-capacity, high-density artificial graphite negative electrode materials.
[0009] The high capacity of the graphite negative electrode material obtained in CN111792640A is mainly due to the use of high-quality needle coke. Since additives have a certain mass proportion in the graphite negative electrode material and contribute little to the capacity, the addition of additives will cause the capacity to decrease relative to pure needle coke.
[0010] The discharge capacity of the composite microspheres of CN105977473A is greatly improved, but the initial efficiency of the composite material is low due to the large specific surface area of graphene.
[0011] The inventors also found that the coke used to prepare artificial graphite in the above scheme is brittle, and it is difficult to reduce the anisotropy of artificial graphite by spheroidizing the particles through mechanical shaping like natural graphite. In order to improve the disadvantage of high anisotropy of coke powder, spray granulation or mixed stirring granulation is usually used to prepare single particles into secondary particles with good sphericity to solve the problem of large expansion of artificial graphite during the cycle. However, the granulation process and the introduction of binders lead to a decrease in the tap density and capacity of the artificial graphite powder material, which in turn shows poor processing performance, increases the technical difficulty of battery cell production, reduces the battery cell production efficiency, and also reduces the energy density of the battery cell.
[0012] The object of the present invention is to provide a spherical graphite material, a preparation method thereof, a composite graphite material, a negative electrode plate and a battery. The spherical graphite material of the present invention has at least one of the characteristics of high tap density, high degree of graphitization, high purity, and low orientation. When the material is applied to the negative electrode material of a lithium ion battery, it exhibits at least one of the effects of high capacity, high first coulomb efficiency, and excellent expansion performance.
[0013] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides a spherical graphite material that satisfies the following conditions (i) to (iii):
[0015] (i) the r value of the spherical graphite material is greater than 0.7, and the r value is obtained by arbitrarily selecting 20 particles of the spherical graphite material from the SEM image and calculating the average value of the ratio of the maximum inscribed circle diameter to the minimum circumscribed circle diameter of the two-dimensional projection surface thereof;
[0016] (ii) the sphericity of the spherical graphite material is ≥ 0.75;
[0017] (iii) For any cross section of the spherical graphite material particle, 10 30 nm×30 nm regions are randomly selected and TEM images are obtained respectively, wherein the TEM images of no more than 3 regions contain a crystal form change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer.
[0018] The amorphous carbon layer of the spherical graphite material of the present invention is located between two graphite lattice layers.
[0019] The spherical graphite material of the present invention has high sphericity, good fluidity, high tap density and low orientation, thus showing excellent processing performance and low expansion when used as negative electrode material for lithium ion batteries. The graphite material has high graphitization degree and shows high capacity and high initial efficiency when used as negative electrode material for lithium ion batteries.
[0020] And / or, for any cross section of the particle of the spherical graphite material, 10 30nm×30nm regions are randomly selected, and TEM images are obtained respectively, wherein the crystal form change region exists in the TEM images of no more than 2 regions, and preferably the crystal form change region exists in the TEM image of no more than 1 region. In a preferred embodiment, it is preferred that the crystal form change region does not exist in the TEM image of any region. In the present invention, the 10 randomly selected 30nm×30nm regions do not overlap.
[0021] And / or, the carbon plane spacing d of the graphite lattice layer observed by TEM 002 It is 0.3354 to 0.3362 nm, for example, 0.3354 nm, 0.3355 nm, 0.3356 nm, 0.3357 nm, 0.3358 nm, 0.3359 nm, 0.3360 nm, 0.3361 nm or 0.3362 nm.
[0022] And / or, the carbon plane spacing d of the amorphous carbon layer observed by TEM 002 is greater than 0.3440 nm, for example, 0.3445 nm, 0.346 nm, 0.347 nm, 0.348 nm, 0.349 nm, 0.35 nm, 0.352 nm, 0.3544 nm, 0.3568 nm, 0.3570 nm, 0.36 nm or 0.3642 nm, etc., and the carbon plane spacing d of the amorphous carbon layer observed by TEM is preferably 002 Greater than 0.35nm.
[0023] And / or, the stacking thickness of the amorphous carbon layer is greater than 2.2 nm, for example, 2.25 nm, 2.26 nm, 2.28 nm, 2.3 nm, 2.35 nm or 2.4 nm.
[0024] And / or, the r value of the spherical material is ≥0.81, for example: 0.81, 0.83, 0.85, 0.9, 0.93, 0.95, 0.987 or 0.998, etc., preferably, the r value of the spherical graphite material is ≥0.95.
[0025] And / or, the sphericity of the spherical material is ≥0.89, for example: 0.89, 0.9, 0.952, 0.975, 0.98 or 0.99, etc., preferably, the sphericity of the spherical graphite material is ≥0.97.
[0026] And / or, the roundness of the spherical graphite material is ≥0.7, for example: 0.7, 0.75, 0.8, 0.83, 0.85, 0.88 or 0.95, etc., preferably, the roundness of the spherical graphite material is ≥0.83.
[0027] And / or, the microstructure of the spherical graphite material does not conform to a Brooks-Taylor type structure.
[0028] And / or, the specific surface area change rate of the spherical graphite material after 5t compaction treatment is less than 8%, for example: 7.5%, 7.2%, 7%, 6.8%, 6.5%, 5%, 4.2%, etc.
[0029] And / or, the particle size change rate of the spherical graphite material after 5t compaction treatment is less than 5.5%, for example: 5.4%, 5.2%, 5%, 4.8%, 4.3%, 3.9% or 2.8%, etc.
[0030] And / or, the median particle size Dv50 of the spherical graphite material is 7 to 18 μm, for example: 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, etc.
[0031] And / or, the specific surface area of the spherical graphite material is 0.8 to 1.2 m 2 / g, for example: 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g or 1.2m 2 / g, etc.
[0032] And / or, the size La of the crystallites of the spherical graphite material in the plane direction of the carbon hexagonal ring network is 90-150nm, for example: 90nm, 95nm, 100nm, 110nm, 115nm, 120nm, 130nm, 140nm or 150nm, etc.
[0033] And / or, the size Lc of the crystallites of the spherical graphite material in the direction perpendicular to the plane of the carbon hexagonal ring network is 60-115 nm, for example: 60 nm, 65 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm or 115 nm.
[0034] And / or, the ratio of Lc to the median particle size Dv50 of the spherical graphite material is 0.006-0.017, for example: 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016 or 0.017, etc.
[0035] And / or, the tap density of the spherical graphite material is 1.15-1.35 g / cm 3 , for example: 1.15g / cm 3 , 1.2g / cm3 , 1.25g / cm 3 , 1.3g / cm 3 or 1.35g / cm 3 The tap density of the spherical graphite material is preferably 1.2 to 1.35 g / cm 3 .
[0036] And / or, the graphitization degree of the spherical graphite material is 91-96%, for example, 91%, 92%, 93%, 94%, 95% or 96%, etc., preferably, the graphitization degree of the spherical graphite material is 94-95.5%.
[0037] And / or, the orientation of the spherical graphite material is 004 / I 110 is 1.5 to 3.2, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.2, 2.5, 2.8, 3 or 3.2, etc., and the orientation I of the spherical graphite material is preferably 004 / I 110 It is 1.5 to 1.8.
[0038] The spherical graphite material of the present invention has a low orientation degree, indicating that the graphite material has a low degree of anisotropy, which further indicates that it has excellent expansion performance.
[0039] In a second aspect, the present invention provides a method for preparing the spherical graphite material as described in the first aspect, the preparation method comprising the following steps:
[0040] providing a powder of a carbon precursor;
[0041] The powder is transported through a heat treatment zone by an inert carrier gas to perform a high-temperature heat treatment, wherein the temperature of the high-temperature heat treatment is greater than the melting point of graphite;
[0042] After the material obtained by high-temperature heat treatment is cooled, the spherical graphite material is obtained.
[0043] The present invention performs high-temperature heat treatment on the carbon precursor powder. The temperature of the high-temperature heat treatment is greater than the melting point of graphite, so that the coke powder is easily heated up and graphitized. At the same time, the temperature can be higher than the melting point of graphite. The graphite melts in an argon suspension state. The graphite balls formed after cooling have no obvious crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer (under the control of certain process conditions, single-particle graphite balls are formed after cooling). At the same time, the high temperature vaporizes impurities in the carbon source and separates them from the graphite, and high-purity graphite balls are obtained after demagnetization.
[0044] And / or, the carbon precursor includes any one of green coke, calcined coke or metallurgical coke, or a combination of at least two of them.
[0045] And / or, the inert carrier gas comprises argon.
[0046] And / or, the heat treatment area is formed by a heat source, and the heat source includes any one or a combination of at least two of a high-temperature plasma torch, a thermal radiation source or an electromagnetic radiation source. Preferably, the heat source is a high-temperature plasma torch.
[0047] The high-temperature plasma torch generates high-temperature gas through an electric arc and can work in an oxidizing, reducing or inert environment. The thermal radiation source is a light source that converts thermal energy into light energy when the luminous object is in a thermal equilibrium state. The electromagnetic radiation source is made based on the principle of electromagnetic coupling. When two electromagnetic radiation objects are close to each other, electromagnetic coupling will occur. Electromagnetic coupling will cause magnetic flux between them, thereby causing electromagnetic induction and current flow between them, which is then converted into thermal energy.
[0048] The present invention adopts high-temperature plasma to carry out heat treatment on coke powder, which can simultaneously achieve the technical effects of graphitization, spheroidization and impurity separation of coke powder.
[0049] Specifically, the present invention uses high-temperature plasma as a heat source, so that the coke powder is easy to heat up and graphitize, and the temperature can be higher than the melting point of graphite. The graphite melts in the argon suspension state, and the graphite balls formed after cooling have no obvious crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer. At the same time, the high temperature vaporizes the impurities in the carbon source and separates them from the graphite, and high-purity graphite balls are obtained after demagnetization. Because the spherical powder has good fluidity, the graphite material obtained by the present invention has at least one of the characteristics of high tap density and small orientation, showing excellent processing performance, and exhibiting low expansion characteristics when applied to lithium-ion battery negative electrode materials; and because the temperature of high-temperature plasma heat treatment is higher than the conventional graphitization temperature, and is carried out in an argon environment, the graphite material obtained by the present invention has a high degree of graphitization, and exhibits high capacity and high initial efficiency when applied to lithium-ion battery negative electrode materials. The production process involved in the present invention is simple, can be produced continuously, has a short production cycle, low consumption, low cost, and is suitable for industrial production.
[0050] And / or, the temperature of the high temperature heat treatment is 3700-4200°C, for example: 3700°C, 3800°C, 3900°C, 4000°C, 4100°C or 4200°C.
[0051] And / or, the material conveying speed of the powder is 5 to 400 g / min, for example: 5 g / min, 10 g / min, 60 g / min, 80 g / min, 100 g / min, 200 g / min, 300 g / min or 400 g / min, etc.
[0052] In a third aspect, the present invention provides a composite graphite material, wherein particles of the composite graphite material include a core and a shell, wherein the core includes at least one particle of the spherical graphite material as described in the first aspect, and the shell is an amorphous carbon layer.
[0053] In the present invention, the carbon-coated amorphous carbon layer has the effect of improving desolvation, thereby improving the overall kinetic performance (ie, rate performance) of the material, and can also reduce the occurrence of side reactions, thereby improving the cycle.
[0054] In a fourth aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the spherical graphite material as described in the first aspect or the composite graphite material as described in the third aspect.
[0055] In a fifth aspect, the present invention provides a battery, comprising the negative electrode plate as described in the fourth aspect.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The spherical graphite material of the present invention has high sphericity, good fluidity, at least one of the following characteristics: high tap density, low orientation, etc., exhibits excellent processing performance, and exhibits low expansion characteristics when used as negative electrode materials for lithium-ion batteries. The graphite material has a high degree of graphitization, and exhibits high capacity and high initial efficiency characteristics when used as negative electrode materials for lithium-ion batteries.
[0058] (2) The present invention uses high-temperature plasma to heat-treat the focused powder to obtain artificial graphite with good sphericity. The particles of the graphite material have no obvious crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer (under certain process conditions, single-particle graphite balls are formed after cooling). In addition, the graphite material has at least one of the following characteristics: high tap density, high degree of graphitization, high purity, and low orientation. When the material is used as a negative electrode material for lithium-ion batteries, it exhibits high capacity, high first coulomb efficiency, and excellent expansion performance.
[0059] (3) In a preferred embodiment, the sphericity of the spherical graphite material of the present invention can reach above 0.97, the roundness can reach above 0.83, the r value can reach above 0.95, the particle size change rate after 5t compaction treatment can reach below 5.2%, the BET change rate can reach below 7.6%, and the tap density can reach 1.21g / cm 3 Above, the graphitization degree can reach more than 94.1%, I 004 / I 110The ratio of Lc to Dv50 is 1.5 to 1.8, the ratio of Lc to Dv50 is 0.06 to 0.017, the particle morphology is single particle, the microstructure of the spherical graphite material does not conform to the Brooks-Taylor structure, the capacity of the prepared battery can reach more than 355.4 mAh / g, and the first efficiency can reach more than 94.3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is the SEM image of the spherical graphite material described in Example 1.
[0061] Figure 2 This is a TEM image of a partial area of the spherical graphite material described in Example 1.
[0062] Figure 3 It is a schematic diagram of graphite lattice layer-amorphous carbon layer-graphite lattice layer.
[0063] Figure 4 It is a schematic diagram of the two-dimensional projection surface of graphite particles. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] In one embodiment, the present invention provides a spherical graphite material that satisfies the following conditions (i) to (iii):
[0066] (i) the r value of the spherical graphite material is greater than 0.7, and the r value is obtained by arbitrarily selecting 20 particles of the spherical graphite material from the SEM image and calculating the average value of the ratio of the maximum inscribed circle diameter to the minimum circumscribed circle diameter of the two-dimensional projection surface thereof;
[0067] (ii) the sphericity of the spherical graphite material is ≥ 0.75;
[0068] (iii) For any cross section of the spherical graphite material particle, 10 30 nm×30 nm regions are randomly selected and TEM images are obtained respectively, wherein the TEM images of no more than 3 regions contain a crystal form change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer.
[0069] The amorphous carbon layer region of the spherical graphite material of the present invention is located between two graphite lattice layer regions.
[0070] The spherical graphite material of the present invention has high sphericity, good fluidity, high tap density and low orientation, thus showing excellent processing performance and low expansion when used as negative electrode material for lithium ion batteries. The graphite material has high graphitization degree and shows high capacity and high initial efficiency when used as negative electrode material for lithium ion batteries.
[0071] And / or, for any cross section of the particle of the spherical graphite material, 10 30nm×30nm regions are randomly selected, and TEM images are obtained respectively, wherein the crystal form change region exists in the TEM images of no more than 2 regions, and preferably the crystal form change region exists in the TEM image of no more than 1 region. In a preferred embodiment, it is preferred that the crystal form change region does not exist in the TEM image of any region. In the present invention, the 10 randomly selected 30nm×30nm regions do not overlap.
[0072] And / or, the carbon plane spacing d of the graphite lattice layer observed by TEM 002 It is 0.3354 to 0.3362 nm, for example, 0.3354 nm, 0.3355 nm, 0.3356 nm, 0.3357 nm, 0.3358 nm, 0.3359 nm, 0.3360 nm, 0.3361 nm or 0.3362 nm.
[0073] And / or, the carbon plane spacing d of the amorphous carbon layer observed by TEM 002 is greater than 0.3440 nm, for example, 0.3445 nm, 0.346 nm, 0.347 nm, 0.348 nm, 0.349 nm, 0.35 nm, 0.352 nm, 0.3544 nm, 0.3568 nm, 0.3570 nm, 0.36 nm or 0.3642 nm, etc., and the carbon plane spacing d of the amorphous carbon layer observed by TEM is preferably 002 Greater than 0.35nm.
[0074] And / or, the stacking thickness of the amorphous carbon layer is greater than 2.2 nm, for example, 2.25 nm, 2.26 nm, 2.28 nm, 2.3 nm, 2.35 nm or 2.4 nm.
[0075] And / or, the r value of the spherical material is ≥0.81, for example: 0.81, 0.83, 0.85, 0.9, 0.93, 0.95, 0.987 or 0.998, etc., preferably, the r value of the spherical graphite material is ≥0.95.
[0076] And / or, the sphericity of the spherical material is ≥0.89, for example: 0.89, 0.9, 0.952, 0.975, 0.98 or 0.99, etc., preferably, the sphericity of the spherical graphite material is ≥0.97.
[0077] And / or, the roundness of the spherical graphite material is ≥0.7, for example: 0.7, 0.75, 0.8, 0.83, 0.85, 0.88 or 0.95, etc., preferably, the roundness of the spherical graphite material is ≥0.83.
[0078] And / or, the microstructure of the spherical graphite material does not conform to a Brooks-Taylor type structure.
[0079] And / or, the specific surface area change rate of the spherical graphite material after 5t compaction treatment is less than 8%, for example: 7.5%, 7.2%, 7%, 6.8%, 6.5%, 5%, 4.2%, etc.
[0080] And / or, the particle size change rate of the spherical graphite material after 5t compaction treatment is less than 5.5%, for example: 5.4%, 5.2%, 5%, 4.8%, 4.3%, 3.9% or 2.8%, etc.
[0081] And / or, the median particle size Dv50 of the spherical graphite material is 7 to 18 μm, for example: 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, etc.
[0082] And / or, the specific surface area of the spherical graphite material is 0.8 to 1.2 m 2 / g, for example: 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g or 1.2m 2 / g, etc.
[0083] And / or, the size La of the crystallites of the spherical graphite material in the plane direction of the carbon hexagonal ring network is 90-150nm, for example: 90nm, 95nm, 100nm, 110nm, 115nm, 120nm, 130nm, 140nm or 150nm, etc.
[0084] And / or, the size Lc of the crystallites of the spherical graphite material in the direction perpendicular to the plane of the carbon hexagonal ring network is 60-115 nm, for example: 60 nm, 65 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm or 115 nm.
[0085] And / or, the ratio of Lc to the median particle size Dv50 of the spherical graphite material is 0.006-0.017, for example: 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016 or 0.017, etc.
[0086] And / or, the tap density of the spherical graphite material is 1.15-1.35 g / cm 3 , for example: 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 or 1.35g / cm 3 The tap density of the spherical graphite material is preferably 1.2 to 1.35 g / cm 3 .
[0087] And / or, the graphitization degree of the spherical graphite material is 91-96%, for example, 91%, 92%, 93%, 94%, 95% or 96%, etc., preferably, the graphitization degree of the spherical graphite material is 94-95.5%.
[0088] And / or, the orientation of the spherical graphite material is 004 / I 110 is 1.5 to 3.2, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.2, 2.5, 2.8, 3 or 3.2, etc., and the orientation I of the spherical graphite material is preferably 004 / I 110 It is 1.5 to 1.8.
[0089] The spherical graphite material of the present invention has a low orientation degree, indicating that the graphite material has a low degree of anisotropy, which further indicates that it has excellent expansion performance.
[0090] In one embodiment, the present invention provides a method for preparing the spherical graphite material as described above, the preparation method comprising the following steps:
[0091] providing a powder of a carbon precursor;
[0092] The powder is transported through a heat treatment zone by an inert carrier gas to perform a high-temperature heat treatment, wherein the temperature of the high-temperature heat treatment is greater than the melting point of graphite;
[0093] After the material obtained by high-temperature heat treatment is cooled, the spherical graphite material is obtained.
[0094] The present invention performs high-temperature heat treatment on the carbon precursor powder. The temperature of the high-temperature heat treatment is greater than the melting point of graphite, so that the coke powder is easily heated up and graphitized. At the same time, the temperature can be higher than the melting point of graphite. The graphite melts in an argon suspension state. The graphite balls formed after cooling have no obvious crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer (under the control of certain process conditions, single-particle graphite balls are formed after cooling). At the same time, the high temperature vaporizes impurities in the carbon source and separates them from the graphite, and high-purity graphite balls are obtained after demagnetization.
[0095] And / or, the carbon precursor includes any one of green coke, calcined coke or metallurgical coke, or a combination of at least two of them.
[0096] And / or, the inert carrier gas comprises argon.
[0097] And / or, the heat treatment area is formed by a heat source, and the heat source includes any one or a combination of at least two of a high-temperature plasma torch, a thermal radiation source or an electromagnetic radiation source. Preferably, the heat source is a high-temperature plasma torch.
[0098] The high-temperature plasma torch generates high-temperature gas through an electric arc and can work in an oxidizing, reducing or inert environment. The thermal radiation source is a light source that converts thermal energy into light energy when the luminous object is in a thermal equilibrium state. The electromagnetic radiation source is made based on the principle of electromagnetic coupling. When two electromagnetic radiation objects are close to each other, electromagnetic coupling will occur. Electromagnetic coupling will cause magnetic flux between them, thereby causing electromagnetic induction and current flow between them, which is then converted into thermal energy.
[0099] The present invention adopts high-temperature plasma to carry out heat treatment on coke powder, which can simultaneously achieve the technical effects of graphitization, spheroidization and impurity separation of the coke powder.
[0100] Specifically, the present invention uses high-temperature plasma as a heat source, so that the coke powder is easy to heat up and graphitize, and the temperature can be higher than the melting point of graphite. The graphite melts in the argon suspension state, and the graphite balls formed after cooling have no obvious crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer. At the same time, the high temperature vaporizes the impurities in the carbon source and separates them from the graphite, and high-purity graphite balls are obtained after demagnetization. Because the spherical powder has good fluidity, the graphite material obtained by the present invention has at least one of the characteristics of high tap density and small orientation, showing excellent processing performance, and exhibiting low expansion characteristics when applied to lithium-ion battery negative electrode materials; and because the temperature of high-temperature plasma heat treatment is higher than the conventional graphitization temperature, and is carried out in an argon environment, the graphite material obtained by the present invention has a high degree of graphitization, and exhibits high capacity and high initial efficiency when applied to lithium-ion battery negative electrode materials. The production process involved in the present invention is simple, can be produced continuously, has a short production cycle, low consumption, low cost, and is suitable for industrial production.
[0101] And / or, the temperature of the high temperature heat treatment is 3700-4200°C, for example: 3700°C, 3800°C, 3900°C, 4000°C, 4100°C or 4200°C.
[0102] And / or, the material conveying speed of the powder is 5 to 400 g / min, for example: 5 g / min, 10 g / min, 60 g / min, 80 g / min, 100 g / min, 200 g / min, 300 g / min or 400 g / min, etc.
[0103] In one embodiment, the present invention provides a composite graphite material, wherein particles of the composite graphite material include a core and a shell, wherein the core includes at least one particle of the spherical graphite material as described above, and the shell is an amorphous carbon layer.
[0104] In the present invention, the carbon-coated amorphous carbon layer has the effect of improving desolvation, thereby improving the overall kinetic performance (ie, rate performance) of the material, and can also reduce the occurrence of side reactions, thereby improving the cycle.
[0105] In one embodiment, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the spherical graphite material as described above or the composite graphite material as described above.
[0106] In one embodiment, the present invention provides a battery, wherein the battery comprises the negative electrode plate as described above.
[0107] The present invention adopts the following method to test the materials obtained in the embodiments and comparative examples:
[0108] (1) The particle size of the sample was tested by Malvern laser particle size analyzer (MS3000), with a light shielding rate of 8-12% and water as the test medium. For the samples treated with 5 tons of compaction, the samples were first subjected to ultrasonic pretreatment at 53kHz for 20 minutes before the particle size test. The ultrasonic medium was water, and the mass ratio of water to sample was 200:1. The median particle size of the sample before 5 tons of compaction was recorded as Dv50; the median particle size of the sample after 5 tons of compaction was recorded as Dv'50. The rate of change of the particle size was calculated by subtracting the difference between Dv50 and Dv'50 and then dividing it by Dv50.
[0109] (2) The specific surface area of the sample is measured in accordance with the provisions of GB / T 19587; the specific surface area of the sample before 5 tons compaction treatment is recorded as BET1; the median particle size of the sample after 5 tons compaction treatment is recorded as BET2, and the BET change rate is calculated by subtracting BET1 from BET2 and dividing it by BET1.
[0110] (3) The sample powder is loaded into a mold and subjected to powder compaction treatment under 5 ton conditions using a universal material testing machine;
[0111] (4) The graphitization degree and tap density of the sample were measured according to the method described in GB / T 24533-2019;
[0112] (5) The ash content of the sample shall be determined according to the method described in YS / T 63.19-2012;
[0113] (6) Graphite orientation test: The sample was scanned by XRD spectrum. The X-ray diffractometer used a copper target with a wavelength of 0.154056 nm and a scanning speed of about 4° / min. The spectrum information such as d was obtained by analysis software such as HighScore Plus and Jade. 002 The crystallite size Lc and La are calculated by using the Scherrer formula as the formula for calculating the crystallite size. The orientation of graphite is determined by the ratio of the peak intensity of the (004) peak near 54.5° to the peak intensity of the (110) peak near 77.7°. 004 / I 110 ;
[0114] (7) Observe the surface morphology of the graphite sample by scanning electron microscopy;
[0115] (8) The microstructure of the graphite sample was observed by transmission electron microscopy. The sample preparation method was to slice the graphite powder with an ultrathin slicer, randomly select ultrathin slices for conventional sample preparation and observation with a transmission electron microscope, and observe and photograph the lattice fringes under the condition that the field of view was enlarged to not less than 30nm*30nm. The field of view was moved and 10 pictures were randomly obtained.
[0116] (9) Sphericity and roundness statistics: 100 particle samples were randomly selected from the SEM images, and the sizes of the major axis a and the minor axis b of the particles were measured. The sphericity R is the ratio of the minor axis to the major axis, that is, R = b / a. The result was averaged. The higher the sphericity, the larger the value. The two-dimensional projection circumference L and area S of the particles were measured. The roundness r is 4 times the product of the two-dimensional projection area and pi divided by the square of its two-dimensional projection circumference, that is, r = 4πS / L 2 , the result is averaged. From this calculation formula, it can be seen that when the two-dimensional projection of the particle is a standard circle, r = 1, otherwise it is less than 1. The better the roundness, the larger the value;
[0117] (10) The maximum inscribed circle diameter and the minimum circumscribed circle diameter of the two-dimensional projection surface of the particle are obtained by calculation (the two-dimensional projection surface of the particle is a subset of the minimum circumscribed circle, and the maximum inscribed circle is a subset of the two-dimensional projection surface of the particle, as shown in the schematic diagram Figure 4 For the same sample, 20 particles were calculated and the average value was taken.
[0118] (11) Electrochemical performance test: According to the negative electrode material: CMC: SP: SBR = 93.5:1.5:2:3, the negative electrode sheet was coated, dried, and rolled to prepare a CR2430 button half-cell, and the counter electrode was a metal lithium sheet. The first lithium removal capacity and the first coulomb efficiency of the negative electrode material were tested. The button half-cell was discharged at 0.1C to 0.005V, left to stand for 10min, discharged at 0.01C to 0.005V, left to stand for 10min, and then charged at 0.1C to 2V.
[0119] Example 1
[0120] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0121] (1) Raw coke powder with a particle size Dv50 of 9 μm is passed through a high-temperature plasma torch area at a rate of 60 g / min under the combined action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 4000°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0122] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0123] The SEM image of the spherical graphite material is as follows Figure 1 As shown by Figure 1 It can be seen that the graphite material prepared by the method of the present invention has a higher sphericity.
[0124] For any cross section of the spherical graphite material particle, 10 30nm×30nm regions are randomly selected and TEM images are obtained respectively (one TEM image is as follows: Figure 2 As shown in the figure, there is no crystal form change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer. For the crystal form change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer, Figure 3 A schematic diagram of a typical crystal phase change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer is shown, wherein the stacking thickness of the amorphous carbon layer is greater than 2.2 nm. Figure 2 Obvious graphite lattice stripes are visible, and there is no amorphous carbon layer with a stacking thickness greater than 2.2 nm, that is, there is no crystal change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer.
[0125] Example 2
[0126] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0127] (1) The calcined coke powder with a particle size Dv50 of 6 μm is passed through the high-temperature plasma torch area at a rate of 10 g / min under the joint action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 3900°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0128] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0129] Example 3
[0130] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0131] (1) Calcined coke powder with a particle size Dv50 of 20 μm is passed through a high-temperature plasma torch area at a rate of 300 g / min under the combined action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 4200°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0132] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0133] Example 4
[0134] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0135] (1) Raw coke powder with a particle size Dv50 of 9 μm is passed through a high-temperature plasma torch area at a rate of 60 g / min under the combined action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 3300°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0136] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0137] Example 5
[0138] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0139] (1) Raw coke powder with a particle size Dv50 of 9 μm is passed through a high-temperature plasma torch area at a rate of 60 g / min under the combined action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 4500°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0140] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0141] Example 6
[0142] This embodiment provides a spherical graphite material, and the spherical graphite material is prepared by the following method:
[0143] (1) Raw coke powder with a particle size Dv50 of 9 μm is passed through a high-temperature plasma torch area at a rate of 420 g / min under the combined action of a material conveyor and a jet pipe containing argon gas. The outer flame temperature of the plasma torch is controlled at about 4000°C. After passing through the plasma torch area, the material enters a pipeline with an interlayer coolant along with the air flow for cooling, and then the graphite powder flows into a material collection bin;
[0144] (2) The material in the material collection bin is demagnetized using a demagnetizer with a magnetic induction intensity of 10000 Gs to obtain the spherical graphite material.
[0145] Comparative Example 1
[0146] This comparative example provides a graphite material, which is prepared by the following method:
[0147] The raw coke powder with a particle size Dv50 of 9 μm is graphitized in an Acheson furnace with a maximum graphitization temperature of 3000° C. After the material is cooled, an artificial graphite negative electrode material is obtained.
[0148] Comparative Example 2
[0149] This comparative example provides a spherical graphite material, which is prepared by the following method:
[0150] The raw coke powder with a particle size Dv50 of 9 μm and the asphalt powder with a particle size Dv50 of 7 μm are mixed in a mass ratio of 20:1, and then the mixture is put into a reactor. Under nitrogen protection, the temperature is increased to 700°C at a rate of 10°C / min and kept for 1 hour to carry out a granulation reaction. The granulated material is graphitized in an Acheson furnace with a maximum graphitization temperature of 3000°C. After the material is cooled, the spherical graphite material is obtained.
[0151] Comparative Example 3
[0152] This comparative example provides a spherical graphite material, which is prepared by the following method:
[0153] Raw coke powder with a particle size Dv50 of 9 μm, cellulose, polyvinyl pyrrolidone and water are mixed in a mass ratio of 10:1:1:100 and stirred at 90°C for 1 hour to prepare a slurry. The slurry is spray granulated by a spray dryer, and the spray drying inlet temperature is 240°C. Microspheres are obtained after the material is cooled, and then the microspheres are graphitized by an Acheson furnace, and the maximum graphitization temperature is 3000°C. After the material is cooled, the spherical graphite material is obtained.
[0154] Comparative Example 4
[0155] The difference between this comparative example and Example 1 is that the material used is mesophase carbon microspheres with a sphericity of 0.97 as the raw material, and the other steps and parameters are consistent with Example 1.
[0156] Performance Test:
[0157] The specific test results of the materials described in the embodiments and comparative examples are shown in Table 1-2:
[0158] Table 1
[0159]
[0160]
[0161] Table 2
[0162]
[0163] As can be seen from Table 1-2 and from Examples 1-3, the present invention uses high-temperature plasma to heat-treat the coke powder to obtain single-particle artificial graphite with good sphericity. In addition, the graphite material has the characteristics of high tap density, high graphitization degree, high purity, and low orientation. When the material is used as a negative electrode material for lithium-ion batteries, it exhibits high capacity, high first coulomb efficiency, and excellent expansion performance. The sphericity of the spherical graphite material obtained by the method can reach above 0.97, the roundness can reach above 0.83, the r value can reach above 0.95, the particle size change rate can reach below 5.2% after 5t compaction treatment, the BET change rate can reach below 7.6%, and the tap density can reach 1.21g / cm 3 Above, the graphitization degree can reach more than 94.1%, I 004 / I 110The ratio of Lc to Dv50 is 1.5 to 1.8, the ratio of Lc to Dv50 is 0.06 to 0.017, the particle morphology is single particle, the microstructure of the spherical graphite material does not conform to the Brooks-Taylor structure, the capacity of the prepared battery can reach more than 355.4 mAh / g, and the first efficiency can reach more than 94.3%.
[0164] It can be seen from Examples 1-6 that when the plasma temperature is high and the obtained sample has a smaller BET and a higher roundness, the first coulomb efficiency of the sample is higher. The sample obtained by the present invention has a higher crystallite size Lc and La, and the ratio of Lc to Dv50 is ≥0.0062, but ≤0.0167. The particle size change rate of the sample after 5t pressure treatment is ≤5.2%, and the BET change rate is ≤7.6% (because the sample has a higher sphericity and the high heat treatment temperature makes the sample structure more uniform, so that the sample has a stronger ability to resist mechanical crushing, so that the sample particle size after pressure treatment is not significantly reduced, and the BET increase is not significant); the cross-sectional thin slices of the sample obtained in the present technical scheme are observed using a projection electron microscope, and it is difficult to find obvious "graphite lattice stripes-amorphous carbon layer-graphite lattice stripes" areas (i.e., graphite lattice layer-amorphous carbon layer-graphite lattice layer crystal change area), this type of area is commonly found in secondary particles granulated by a single particle with a binder, even the secondary particles observed under SEM conditions of the graphite obtained in Example 5 of the present invention are composite particles formed by the melting of two or more particles and are morphologically similar to secondary particles, and the composite particles are formed in a molten state without the addition of a binder, and thus have no obvious "graphite lattice stripes-amorphous carbon layer-graphite lattice stripes" area (crystal change area).
[0165] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the spherical graphite material of the present invention, the temperature of the high-temperature heat treatment will affect its performance. When the temperature of the high-temperature heat treatment is controlled at 3700-4200°C, the performance of the graphite material obtained is better. When the temperature is too low, although the coke powder can be graphitized, the temperature is not enough to make the temperature of the graphite particles reach the melting point of graphite, so the edges of the graphite particles cannot be rounded, that is, the graphite particles cannot be spheroidized; when the outer flame temperature of the plasma torch is too high, it is easy to cause the adhesion between the graphite particles to form secondary particles, thereby reducing the tap density.
[0166] By comparing Example 1 and Example 6, it can be seen that in the preparation process of the spherical graphite material described in the present invention, the temperature of the high-temperature heat treatment will affect its performance, and the material conveying speed will affect the performance of the spherical graphite material obtained. When the material conveying speed is too fast, the total amount of heat conduction units is insufficient, so that the coke powder cannot reach the melting temperature, and the sphericity of the obtained graphite is not high.
[0167] From the comparison between Example 1 and Comparative Example 1, it can be seen that the present invention uses high-temperature plasma to heat-treat the coking powder, which is beneficial to the spheroidization and high-degree graphitization of artificial graphite particles, and increases the tap density and capacity of graphite, thereby improving its processing performance.
[0168] By comparing Example 1 and Comparative Example 2, it can be seen that the present invention uses high-temperature plasma to heat-treat the coke powder, which can prepare single-particle spherical artificial graphite and improve the tap density and capacity of the graphite; and although asphalt as a binder is used to granulate the coke powder, the sphericity of the graphite particles can be improved, but the obtained graphite particles are secondary particles composed of single particles, which results in the tap density and capacity of the spherical artificial graphite negative electrode material prepared by granulation being inferior to the spherical artificial graphite negative electrode material provided by the scheme of the present invention.
[0169] By comparing Example 1 and Comparative Example 3, it can be seen that the present invention uses high-temperature plasma to heat-treat the coking powder, which can prepare single-particle spherical artificial graphite and improve the tap density and capacity of the graphite; although spray granulation can improve the sphericity of the graphite particles, the aggregate particle size is too large and a relatively excellent sphericity cannot be obtained. The obtained graphite particles are secondary particles composed of single particles. Dispersants and binders are added when preparing the spray slurry. These result in the tap density and capacity of the spherical artificial graphite negative electrode material prepared by spraying are not as good as the spherical artificial graphite negative electrode material provided by the scheme of the present invention.
[0170] From the comparison between Example 1 and Comparative Example 4, it can be seen that the artificial graphite negative electrode material prepared by heat treating the coke powder with high temperature plasma in the present invention has a capacity advantage. This is related to the fact that the mesophase carbon microspheres have a lamellar structure arranged along the latitude when they are in the green state. After plasma heat treatment under the same conditions, the coke powder is more likely to obtain a higher degree of graphitization.
[0171] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A spherical graphite material, characterized in that: The following conditions (i) to (iii) are met: (i) the r value of the spherical graphite material is greater than 0.7, and the r value is obtained by arbitrarily selecting 20 particles of the spherical graphite material from the SEM image and calculating the average value of the ratio of the maximum inscribed circle diameter to the minimum circumscribed circle diameter of the two-dimensional projection surface thereof; (ii) the sphericity of the spherical graphite material is ≥ 0.75; (iii) For any cross section of the spherical graphite material particle, 10 30 nm×30 nm regions are randomly selected and TEM images are obtained respectively, wherein the TEM images of no more than 3 regions contain a crystal form change zone of graphite lattice layer-amorphous carbon layer-graphite lattice layer.
2. The spherical graphite material according to claim 1, characterized in that For any cross section of the particle of the spherical graphite material, 10 30 nm×30 nm regions are randomly selected, and TEM images are obtained respectively, wherein the crystal form change region exists in the TEM images of no more than 2 regions, and preferably the crystal form change region exists in the TEM images of no more than 1 region; And / or, the carbon plane spacing d of the graphite lattice layer observed by TEM 002 0.3354~0.3362nm; And / or, the carbon plane spacing d of the amorphous carbon layer observed by TEM 002 The carbon surface spacing d of the amorphous carbon layer observed by TEM is preferably greater than 0.3440 nm. 002 Greater than 0.35nm; And / or, the stacking thickness of the amorphous carbon layer is greater than 2.2 nm; and / or, the r value of the spherical material is ≥ 0.81, preferably the r value of the spherical graphite material is ≥ 0.95; and / or, the sphericity of the spherical material is ≥ 0.89, preferably the sphericity of the spherical graphite material is ≥ 0.97; And / or, the roundness of the spherical graphite material is ≥ 0.7, preferably the roundness of the spherical graphite material is ≥ 0.83; And / or, the microstructure of the spherical graphite material does not conform to a Brooks-Taylor type structure.
3. The spherical graphite material according to claim 1 or 2, characterized in that: The specific surface area change rate of the spherical graphite material after 5t compaction treatment is less than 8%; And / or, the particle size change rate of the spherical graphite material after 5t compaction treatment is less than 5.5%; And / or, the median particle size Dv50 of the spherical graphite material is 7 to 18 μm; And / or, the specific surface area of the spherical graphite material is 0.8 to 1.2 m 2 / g.
4. The spherical graphite material according to any one of claims 1 to 3, characterized in that: The size La of the microcrystals of the spherical graphite material in the plane direction of the carbon hexagonal ring network is 90 to 150 nm; And / or, the size Lc of the microcrystals of the spherical graphite material in the direction perpendicular to the plane of the carbon hexagonal ring network is 60 to 115 nm; and / or, the ratio of Lc to the median particle size Dv50 of the spherical graphite material is 0.006 to 0.017; And / or, the tap density of the spherical graphite material is 1.15-1.35 g / cm 3 Preferably, the tap density of the spherical graphite material is 1.2 to 1.35 g / cm 3 ; And / or, the graphitization degree of the spherical graphite material is 91-96%, preferably the graphitization degree of the spherical graphite material is 94-95.5%; And / or, the orientation of the spherical graphite material is 004 / I 110 is 1.5 to 3.2, and the orientation I of the spherical graphite material is preferably 004 / I 110 It is 1.5 to 1.
8.
5. A method for preparing the spherical graphite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: providing a powder of a carbon precursor; The powder is transported through a heat treatment zone by an inert carrier gas to perform a high-temperature heat treatment, wherein the temperature of the high-temperature heat treatment is greater than the melting point of graphite; After the material obtained by high-temperature heat treatment is cooled, the spherical graphite material is obtained.
6. The preparation method according to claim 5, characterized in that: The carbon precursor includes any one of green coke, calcined coke or metallurgical coke, or a combination of at least two thereof; And / or, the inert carrier gas comprises argon.
7. The preparation method according to claim 5 or 6, characterized in that: The heat treatment area is formed by a heat source, which includes any one or a combination of at least two of a high-temperature plasma torch, a thermal radiation source or an electromagnetic radiation source, and preferably the heat source is a high-temperature plasma torch; And / or, the temperature of the high temperature heat treatment is 3700-4200°C; And / or, the material conveying speed of the powder is 5 to 400 g / min.
8. A composite graphite material, characterized in that: The particles of the composite graphite material include a core and a shell layer, the core includes at least one particle of the spherical graphite material according to any one of claims 1 to 4, and the shell layer is an amorphous carbon layer.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the spherical graphite material according to any one of claims 1 to 4 or the composite graphite material according to claim 8.
10. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Carbon / carbon composite microsphere material, production method and lithium ion battery
CN103214245A
Isotropic graphite / graphene composite microsphere negative electrode material and preparation method thereof
CN105977473A
Spherical-like low-expansion high-capacity graphite negative electrode material and preparation method thereof, and lithium ion battery
CN111792640A
Cited By
Active material, negative electrode sheet, battery and electric equipment
EP4811441A1